Character Design for Interactive Pop-Up Storybook as Emotional Regulation Learning Media for Marginal Children - Indra, Diva Irmaliya; Sutejo, Aris; Masnuna, Masnuna (Journal of Visual Communication Design, 2026)
Children's emotional regulation is crucial for psychological well-being and social development, yet marginalized children in Indonesia remain vulnerable due to socioeconomic pressures and limited access to interventions. Existing studies have primarily focused on facilitator-oriented training modules that emphasize rules and activity flow. These are not easily accessible to children, lack visual appeal, and are hampered by time, resources, and technical requirements for training sessions. This creates a gap in non-digital, interactive visual media that children can use independently to memorize and practice emotion regulation strategies while gaining a comparable learning experience. Addressing this gap, the present study aims to design character representations for an interactive pop-up storybook as a self-learning tool, facilitated by the WE POSE Surabaya community. Employing a qualitative Design Thinking approach through interviews with children aged 8–10, expert validation, and a literature review. This exploration resulted in four characters: Jalu, Tilu, Bara, and Laras. Warm color tones and chromatic shifts were applied to intuitively represent the emotional context. This storybook integrates interactive features such as pop-up scenes, liftable flaps, and pull-out tabs, allowing children to actively engage. The findings suggest that this type of interactive storybook can serve as an inclusive educational medium for marginalized children with limited digital access. This research contributes to Visual Communication Design by combining character design with physical interactivity to strengthen learning outcomes on emotion regulation.